High‐Efficiency Photovoltaic Conversion at Selective Electron Tunneling Heterointerfaces. (21st September 2017) - Jia, Chuancheng; Ma, Wei; Guan, Jianxin; Gu, Chunhui; Li, Xinxi; Meng, Linan; Gong, Yao; Meng, Sheng; Guo, Xuefeng
Abstract: Effectively controlling photoinduced charge transport at the heterointerface is of crucial importance for improving the performance of photovoltaic devices. On the basis of an ipsilateral selective electron tunneling (ISET) mechanism, here this study investigates photoinduced charge transport and photovoltaic conversion at a simplified dye/single‐layer graphene (SLG)/TiO2 ternary interface. With an amphiphilic Z907 molecule as the model dye, the photoexcited electrons in the dye can directly tunnel across SLG and be collected by the TiO2 layer with an efficiency of 96.23%, which guarantees a high‐efficiency photoelectric conversion at the ISET‐based heterointerface. More importantly, the intrinsic Schottky barrier and fast hole collection rate at the heterointerface lead to a high photovoltage, a large fill factor, and the good intense‐light performance for photovoltaic conversion. Such an ISET‐based heterointerface may offer a platform of designing and developing a novel class of photovoltaic devices with high efficiency. Abstract : This study investigates photoinduced charge transport and photovoltaic conversion at a simplified dye/graphene/TiO2 ternary interface. With an amphiphilic Z907 molecule as the model dye, photoexcited electrons in the dye can directly tunnel across graphene and can be collected by the TiO2 layer with an efficiency of 96.23%, which guarantees a high‐efficiency photoelectric conversion at the ipsilateral selective electron tunneling based heterointerface.